Wadi Gideah, Oman, Reference Section: Whole rock geochemistry - Dieter Garbe-Schönberg; Jürgen Koepke; Samuel Müller; Dominik Mock; Tim Müller (PANGAEA, 2022)
We sampled outcrops through 6,500 m of fossil oceanic crust in Wadi Gideah (Samail ophiolite, Oman) that is regarded as best analogue of fast-spreading crust on land. To accomplish a comprehensive understanding of accretion processes in the lower crust we follow a multi-technique approach applying petrographic and petrological, microstructural, thermometric, mineral and rock chemical methods to the same samples. Here we report a full set of whole rock major and trace element data displaying systematic and contrasting compositional trends in lower and upper gabbros being correlated with stratigraphic depth in the plutonic suite.